A new genus of Raspy Cricket (Orthoptera: Gryllacrididae: Gryllacridinae: Progryllacridini) from the Brazilian Atlantic Forest - Siqueira, Adriano M.; Ferraz, Bernardo R.; Souza-Dias, Pedro G. B. (Zootaxa, 2025)
In this study, we describe a new monotypic genus of Gryllacrididae from the Atlantic Forest, recorded in the dense ombrophilous forest of the Serra dos Órgãos National Park (Teresópolis, Rio de Janeiro). Diplospinula gen. nov. is assigned to the tribe Progryllacridini and exhibits general morphological traits similar to other apterous/micropterous South American gryllacridids, but can be distinguished primarily by features of the male and female terminalia. We also provide an updated identification key to the apterous/micropterous gryllacridid genera recorded from Brazil.